Full rotationally phase-resolved visible reflectance spectroscopy of 3200 Phaethon. (15th October 2020) - Ohtsuka, Katsuhito; Ito, Takashi; Kinoshita, Daisuke; Abe, Shinsuke; Sawai, Kyosuke; Funabashi, Kazuhiro; Kato, Ryo; Miyasaka, Seidai; Hasegawa, Sunao; Nakamura, Tomoki; Chen, Wen-Ping
Abstract: We present time-series optical spectroscopic observations of 3200 Phaethon during its 2007 return, complemented with R -band photometry. The spectral gradient centered around 0.55 μm varies between − 5.0 % / 0.1 μm and 0.6 % / 0.1 μm, indicating a B- or C-type color. Moreover, rotational modulation of the spectral slope of this asteroid suggests its surface compositional inhomogeneity, particularly the existence of a C-type surface at a certain longitude on this asteroid.